2016
DOI: 10.1103/physrevlett.117.080501
|View full text |Cite
|
Sign up to set email alerts
|

Average-Case Complexity Versus Approximate Simulation of Commuting Quantum Computations

Abstract: We use the class of commuting quantum computations known as IQP (Instantaneous Quantum Polynomial time) to strengthen the conjecture that quantum computers are hard to simulate classically. We show that, if either of two plausible average-case hardness conjectures holds, then IQP computations are hard to simulate classically up to constant additive error. One conjecture relates to the hardness of estimating the complextemperature partition function for random instances of the Ising model; the other concerns ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
548
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 274 publications
(569 citation statements)
references
References 53 publications
13
548
1
Order By: Relevance
“…In 2013, Aaronson and Arkhipov showed this for boson sampling under two conjectures [11]. By generalizing their argument, Bremner et al showed that IQP circuits are unlikely to be simulated classically up to an error in the l 1 norm whose value is constant under only one conjecture [6].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2013, Aaronson and Arkhipov showed this for boson sampling under two conjectures [11]. By generalizing their argument, Bremner et al showed that IQP circuits are unlikely to be simulated classically up to an error in the l 1 norm whose value is constant under only one conjecture [6].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the argument in Ref. [6], in the argument to prove theorem 6, the initial state of each of the ancillary qubits is set to |0 to construct C (2) f . In other words, if we construct C (2) f without setting the initial state of each of them to |0 when f is chosen uniformly at random, we can prove theorem 6 for ǫ =const.…”
Section: Theorem 5 If the Output Probability Distribution Of Any Adiqmentioning
confidence: 99%
See 3 more Smart Citations